Strategies Of Religious Extension In Strengthening Moderate Understanding For The Prevention Of Radicalism And Identity Conflict - Nasihin, Muh; Sulistijanti, Wellie; Setiawan, Rahmat; Suprayitno, Muhammad Robeth; Putri, Meia Rizqi Talitha; Cahyani, Desy Eki (UMSU, 2025)
This study aims to examine the strategies implemented by religious instructors in preventing radicalism and identity friction in four regions in Central Java—Semarang City, Demak Regency, Semarang Regency, and Kendal Regency. Using a qualitative approach with a case study design, data were collected through in-depth interviews and focus group discussions with religious instructors, lecturers, and community leaders to provide in-depth context for local dynamics. The results reveal three complementary clusters of strategies: (1) socializing the value of religious moderation through sermons/lectures, religious study groups, and targeted use of social media; (2) strengthening religious and national literacy through non-formal education such as training, workshops, and interactive forums; and (3) multi-sector collaboration with local governments, religious organizations, and community leaders. However, the implementation of these strategies faces recurring challenges, including limited resources, uneven policy support, and security risks when interacting with intolerant groups. Research findings indicate that the role of religious instructors as key local actors in building social resilience against radicalism is highly strategic, but its effectiveness depends on the integration of educational, collaborative, and contextual approaches supported by sustainable policies and resources.